Simultaneously mastering operando strain and reconstruction effects via phase-segregation strategy for enhanced oxygen-evolving electrocatalysis - Guan, D.; Shi, C.; Xu, Hengyue; Gu, Y.; Zhong, J.; Sha, Y.; Hu, Z.; Ni, M.; Shao, Zongping (2023)
Material strain and reconstruction effects are critical for catalysis reactions, but current insights into operando strain effects during reaction and means to master catalyst reconstruction are still lacking. Here, we propose a facile thermal-induced phase-segregation strategy to simultaneously master material operando strain and reconstruction effects for enhanced oxygen-evolving reaction (OER). Specifically, self-assembled and controllable layered LiCoO2 phase and Co3O4 spinel can be generated from pristine Li2Co2O4 spinel via Li and O volatilization under different temperatures, realizing controllable proportions of two phases by calcination temperature. Combined operando and ex-situ characterizations reveal that obvious tensile strain along (003) plane appears on layered LixCoO2 phase during OER, while low-valence Co3O4 phase transforms into high-valence CoOOHx, realizing simultaneous operando strain and reconstruction effects. Further experimental and computational investigations demonstrate that both strained LixCoO2 phase and reconstructed CoOOHx compound contribute to the beneficial adsorption of important OH− reactants, while respective roles in activity and stability are uncovered by exploring their lattice-oxygen participation mechanism. This work not only reveals material operando strain effects during OER, but also inaugurates a new thermal-induced phase-segregation strategy to artificially master material operando strain and reconstruction effects, which will enlighten rational material design for many potential reactions and applications.